Soil Injection Technology Using an Expandable Polyurethane Resin: A Review - Mohanad Muayad Sabri Sabri (MDPI AG, 2021)
The soil injection, using an expandable polyurethane resin, holds a unique potential for settlement compensation, lifting, and strengthening the foundations of existing buildings and structures. Although various research and case studies regarding this technology have been published, these studies emphasized the technology’s effectiveness in the rapid lifting process. Nevertheless, there is no complete understanding of the technology, yet, that gathers necessary data leading to a better recognition for this technology in the theoretical understanding and the practical applications. This article aims to provide a comprehensive understanding of this technology. The injection process, the resin’s mechanism, and actual propagation in the soil’s massive, the modified physic-mechanical properties of the soil, the expansion process, the consumption of the resin, and the durability are extensively reviewed in this article. Besides that, this article aims to demonstrate the advantages and limitations of this technology in practical applications. The review also explores the existing finite element models used to calculate the strength and stiffness parameters, evaluating the bearing capacity of the composite (soil-resin) and the settlement after the injection process.